ANALISIS INTEGRASI TEKNOLOGI INFORMASI KESEHATAN MOBILE HEALTH BERBASIS DUKUNGAN KELUARGA UNTUK OPTIMALISASI PENGENDALIAN HIPERTENSI DI INDONESIA: STUDI LITERATUR - Jeri Juliandi; Linda Handayuni; Vitratul Ilahi; Nia Watri Wahyuni; Sahaya Putri Destriani; Ade Afdhal Putra; Raisya Hayatun Najmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Hypertension is a non-communicable disease which is the main cause of morbidity and mortality in the world. This disease is known as a silent killer because it often shows no symptoms in the early stages, but can cause serious complications such as heart disease, stroke and kidney failure. Hypertension control does not only depend on pharmacological therapy, but is also influenced by various interrelated multidimensional factors. This research aims to analyze in depth the factors that influence blood pressure control based on literature studies from national journals in the last five years. The method used is a literature study with a qualitative descriptive approach to scientific articles that discuss psychosocial, cognitive and behavioral aspects in hypertension sufferers. The results of the study show that patient motivation, family support, health literacy, as well as diet and physical activity are the main factors that determine the success of controlling blood pressure. The implementation of these factors in the field is currently supported by health technology such as the CERDIKA application with a medication reminder feature and Mobile JKN. These three factors interact with each other and form a complex system in managing hypertension. Therefore, a comprehensive, integrative and sustainable approach is needed. Keywords: hypertension, motivation, health literacy, diet physical activity, mHealth CERDIKA Mobile JKN